The Right Measurements for The Appropriate Interventions: Job Burnout Among Employees in China’s Financial institutions - Jiang Mengmeng; Jakaria Dasan (Universiti Malaysia Sabah, 2022)
Job burnout has been coined as the main cause of turnover cases. Financial institutions in China were not excluded from reporting high case of turnover due to job burnout. The way job burnout was measured were discussed further to identify the appropriate interventions. Hence, literature reviews were carried out from sources of local studies and abroad. Results show that job burnout and external working environment are among the factors influencing employees’ feeling of uneasiness and dissatisfaction leading to job burnout. Unless job burnout is mitigated, China’s financial institutions will keep on facing the shortfall of respective talents.